Chemical and carbon isotope fractionations of alkane gases desorbed from confined systems and the application toward shale gas reservoir. (March 2020) - Liu, Peng; Wang, Xiaofeng; Lin, Ying; Liu, Changjie; Li, Xiaofu; Liu, Wenhui
Abstract: Adsorption and desorption processes of shale gas possess particular characteristics compared to conventional natural gas. Previous studies conducted desorption experiments on fresh core samples to investigate the isotope and chemical fractionations during the desorption process. However, complete chemical and isotope fractionations cannot be obtained due to the loss of gases during the coring process. In this study, we utilized a modified experimental apparatus based on the fixed adsorption bed to conduct systematic desorption experiments in confined systems with different proportions of free and adsorbed gases. The results show that different adsorption capacities and non-synchronous desorption for alkane gas components are leading factors influencing chemical fractionation during the desorption process. Meanwhile, C1 /C2 and C1 /(C1 +C2 ) vary with different proportions of adsorbed gases in the same adsorption matrix. Generally, isotope fractionation between the adsorbed and free phases during desorption follows the Rayleigh fractionation model. The linear correlations between proportions of adsorbed CH4 and isotope fractionation factors can be applied to predict the proportions of adsorbed gases. Calculations show that on average 55% of hydrocarbon gases exist at adsorbed state in shale gas from Yanchang Formation of Ordos Basin. Highlights: A modified experimental apparatus was firstly applied to study the chemical and isotope fractionations during desorption. Isotope fractionation between the adsorbed and free phases during desorption follows the Rayleigh fractionation model. Established mathematical model can be applied to predict the proportion of adsorbed gas in shale.